Implementation of a new algorithm resulting in improvements in accuracy and resolution of SEVIRI hotspot products. Issue 9 (2nd September 2018) - Wickramasinghe, Chathura; Wallace, Luke; Reinke, Karin; Jones, Simon
ABSTRACT: Active wildfire detection, surveillance and mapping is an important application of satellite remote sensing. The Active Fire Monitoring (FIR) products, from the Spinning Enhanced Visible and Infrared Imager (SEVIRI) on board the Meteosat Second Generation (MSG) satellites, provide rapid-fire detection data every 5 to 15 over the European and African continents. However, the real world application of this high temporal frequency data is hindered due to the product spatial resolution of 3 3, thus limiting the application in fire surveillance and mapping activities. This letter implements a modified version of the Advanced Himawari-8 Imager – Fire Surveillance Algorithm (AHI-FSA) for SEVIRI with the aim of improving the spatial resolution of fire activity mapping. Initial results demonstrate the algorithm was able to improve the resolution of fire detection from 3 3 km to 1 1 km and simultaneously reduce the commission and omission errors by 25% and 16% respectively.